Neurotherapeutic Effects of Pueraria mirifica Extract in Early‐ and Late‐Stage Cognitive Impaired Rats. (25th February 2016) - Anukulthanakorn, Kanya; Parhar, Ishwar S.; Jaroenporn, Sukanya; Kitahashi, Takashi; Watanbe, Gen; Malaivijitnond, Suchinda
Abstract : We determined the neurotherapeutic effects of Pueraria mirific a extract (PME) and pure puerarin (PU) in comparison with 17β‐estradiol (E2 ) in early‐ and late‐stage cognitive impaired rats. Rats were ovariectomized (OVX), kept for 2 and 4 months to induce early‐ and late‐stage cognitive impairment, respectively, and divided into four groups that were treated daily with (i) distilled water, (ii) 100 mg/kg of PME, (iii) 7 mg/kg of PU, and (iv) 80 µg/kg of E2 for 4 months. The estrogen deficiency symptoms of OVX rats were abrogated by treatment with E2 or PME, but not by treatment with PU. The mRNA level of genes associated with amyloid production ( App and Bace1 ) and hyperphosphorylated Tau ( Tau4 ) were upregulated together with the level of impaired cognition in the 2‐ and 4‐month OVX rats. Treatment with E2 reduced the level of cognitive impairment more than that with PME and PU, and 2‐month OVX rats were more responsive than 4‐month OVX rats. All treatments down‐regulated the Bace1 mRNA level in 2‐month OVX rats, while PU and PME also decreased the App mRNA level in 2‐ and 4‐month OVX rats, respectively. Only PU suppressed Tau4 expression in 2‐month OVX rats. Thus, PME and PU elicit neurotherapeutic effects in different pathways, and earlier treatment is optimal. Copyright © 2016 John Wiley & Sons, Ltd.